Possible roles for polycomb repressive complex 2 in cereal endosperm - Tonosaki, Kaoru; Kinoshita, Tetsu (Frontiers in Plant Science, 2015)
The Polycomb Repressive Complex 2 (PRC2) is an evolutionarily conserved multimeric protein complex in both plants and animals. In contrast to animals, plants have evolved a range of different components of PRC2 and form diverse complexes that act in the control of key regulatory genes at many stages of development during the life cycle. A number of studies, particularly in the model species Arabidopsis thaliana, have highlighted the role of PRC2 and of epigenetic controls via parent-of-origin specific gene expression for endosperm development. However, recent research in cereal plants has revealed that although some components of PRC2 show evolutionary conservation with respect to parent-of-origin specific gene expression patterns, the identity of the imprinted genes encoding PRC2 components is not conserved. This disparity may reflect the facts that cereal plant genomes have undergone different patterns of duplication during evolution compared to Arabidopsis thaliana and that the endosperm development program is not identical in monocots and eudicots. In this context, we focus this review on the expression of imprinted PRC2 genes and their roles in endosperm development in cereals.